Diseño de una solución innovadora para el fortalecimiento de los procesos comerciales de asociaciones campesinas de Pasto, Nariño (2023)
The purpose of the project is focused on strengthening the commercial processes developed by the peasant associations of the municipality of Pasto, from the design of an innovative solution that impacts the reduction of the problems that currently affect these processes and generate affectation in peasants´ living conditions.